A Systematic Literature Review of Customer Loyalty in Indonesian Private Banking Sector - Wangsitala, Angger; Andriani Kusumawati; Muhammad Kholid Mawardi (Sekolah Pascasarjana Universitas Brawijaya, 2025)
This study presents a systematic literature review to identify the key factors influencing customer loyalty, focusing on ethical behavior, relational benefits, and customer satisfaction. Utilizing the PRISMA framework, a comprehensive search was conducted across multiple online databases, selecting and analyzing 57 relevant articles. The review synthesizes existing empirical evidence to examine how ethical practices—particularly in the banking sector—contribute to building long-term customer relationships. The findings reveal that ethical behavior significantly enhances customer satisfaction, strengthening trust and commitment and ultimately increasing customer loyalty. Relational benefits, such as confidence, social bonds, and special treatment, were also identified as mediating factors that enhance customer retention and encourage positive word-of-mouth. The study highlights the importance of aligning business practices with ethical standards to foster sustainable competitive advantage, particularly in service-oriented industries like banking. Drawing from Stimulus-Organism-Response (SOR) theory, the conceptual framework proposed in this paper illustrates the psychological process through which ethical stimuli influence internal customer states and subsequent behavioral responses. This review contributes to academic knowledge and managerial practice by offering a structured understanding of customer loyalty mechanisms. It also identifies gaps in current research and suggests directions for future studies, particularly in expanding the scope beyond the banking sector and developing more nuanced models of ethical influence in customer relationships.Keywords: customer loyalty, banking, relational benefits, customer satisfaction, systematic review